Organizational Behavior and its Impact on Teacher Burnout in Public Secondary Schools - Moses Adeleke Adeoye; Musa Aremu Mahmud; Hassanat Abdullateef Jimoh; Adeseko Sunday Olaifa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The Nigerian education system faces numerous challenges, including high levels of teacher burnout which adversely affect the quality of education. Understanding the dynamics of organizational behaviour is crucial in addressing these issues and promoting teacher well-being. In the context of education, it involves examining the interactions, attitudes, and behaviours of teachers, administrators, and other stakeholders within the school system. This study analyzes the organizational behaviour and its impact on teacher burnout in Nigeria's public secondary schools. The method used in this research is a systematic literature review. The Researcher collected journal articles from Google Scholar, Research Gate, SINTA, Scopus and Web of Science on existing literature and research on organizational behavior and teacher burnout. Information from selected articles was systematically synthesized to present consistent and in-depth findings on the research topic. The detrimental effects of teacher burnout extend beyond individual teachers and impact student outcomes and the overall quality of education. This study emphasizing the significance of implementing strategies that promote collaboration and collegial support among educators, enhance workload management, provide necessary resources and foster teacher autonomy.